Biomimicking Stretchable Organic Electrochemical Transistor. (8th August 2019) - Li, Yuanzhe; Wang, Naixiang; Yang, Anneng; Ling, Haifeng; Yan, Feng
Abstract: Stretchable organic electrochemical transistors (OECTs) can find applications in wearable electronics for biosensing. However, the existing fabrication methods are either inconvenient or expensive. Here, a novel method to fabricate stretchable OECTs based on biomimicking polydimethylsiloxane substrates is reported. The substrate pattern is transferred from the bract of Bougainvillea glabra, demonstrating a 2D wavy structure. To further enhance the stretchability of the Au electrodes of the devices on the wavy surface, a highly conductive polymer film is coated on the Au surface by inkjet printing to bridge disconnected parts separated by cracks. The obtained OECTs demonstrate omnidirectional stretchability up to 30% and a bending radius down to 15 mm with stable performance. Stretchable glucose sensors with a detection limit around 1 µ m are developed based on the biomimicking stretchable OECTs, which are sensitive enough for detecting glucose levels in body fluids. Abstract : Stretchable organic electrochemical transistors can find applications in wearable biomedical devices. This study develops a novel method to fabricate stretchable devices on biomimicking substrates based on Bougainvillea glabra . The devices prepared by inkjet printing show stable performance with omnidirectional stretchability up to 30% and demonstrate a detection limit of glucose down to 1 µm .